2010
DOI: 10.1159/000313485
|View full text |Cite
|
Sign up to set email alerts
|

Possible Relationship between Neutrophil Gelatinase-Associated Lipocalin, Hepcidin, and Inflammation in Haemodialysed Patients

Abstract: Background: Neutrophil gelatinase-associated lipocalin (NGAL) binds small, iron-carrying molecules – siderophores. On the other hand, hepcidin is a small defensin-like peptide produced by hepatocytes, modulated in response to anaemia, hypoxia, or inflammation. We tested the hypothesis that NGAL may be related to hepcidin, not only to iron metabolism, in 182 prevalent haemodialysed patients. Methods: Iron status (iron, total iron-binding capacity, ferritin, total saturation of transferrin, TSAT), complete blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 87 publications
0
22
0
Order By: Relevance
“…The differences in the GDF15 levels in the controls may be attributed to the age, gender and even iron status. We also found a positive correlation between GDF15 and NGAL (neutrophil gelatinase-associated lipocalin), which is thought to be an acute-phase protein and marker of inflammation [28] and acute kidney injury [29]. NGAL also binds small, iron carrying molecules-siderophores.…”
Section: Discussionmentioning
confidence: 84%
“…The differences in the GDF15 levels in the controls may be attributed to the age, gender and even iron status. We also found a positive correlation between GDF15 and NGAL (neutrophil gelatinase-associated lipocalin), which is thought to be an acute-phase protein and marker of inflammation [28] and acute kidney injury [29]. NGAL also binds small, iron carrying molecules-siderophores.…”
Section: Discussionmentioning
confidence: 84%
“…Recent reports show that decreased serum NGAL levels in hemodialysis patients correlate with higher (total) hepcidin levels and lower TSAT [11,12], suggesting that low serum NGAL levels are associated with reduced iron utilization. Both CKD and CHF are chronic inflammatory conditions in which iron metabolism is disturbed.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Bolignano et al and Malyszko et al suggested that low NGAL levels in hemodialysis patients reflect reduced iron availability and transport; lower NGAL levels were associated with lower transferrin saturation (TSAT), lower ferritin levels and higher hepcidin levels [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…They also proposed that NGAL might be a new tool in the assessment of iron deficiency. In our recent study, we tested the hypothesis that NGAL might be related to hepcidin, not only to iron metabolism prevalent in hemodialyzed patients [47] . We found that in multiple regression analysis, residual renal function, hepcidin, creatinine and hsCRP were predictors of serum NGAL in hemodialyzed patients.…”
Section: Hepcidin and Iron And Ngalmentioning
confidence: 99%